A rare manifestation of STING-associated vasculopathy with onset in infancy: a case report - Sophia Weidler; Sarah Koss; Christine Wolf; Nadja Lucas; Jürgen Brunner; Min Ae Lee-Kirsch (BMC, 2024)
Abstract Background STING-associated vasculopathy with onset in infancy (SAVI) is a rare type I interferonopathy caused by heterozygous variants in the STING gene. In SAVI, STING variants confer a gain-of-function which causes overactivation of type I interferon (IFN) signaling leading to autoinflammation and various degrees of immunodeficiency and autoimmunity. Case presentation We report the case of a 5 year old child and his mother, both of whom presented with systemic inflammatory symptoms yet widely varying organ involvement, disease course and therapeutic response. Genetic testing revealed a heterozygous STING variant, R281Q, in the child and his mother that had previously been associated with SAVI. However, in contrast to previously reported SAVI cases due to the R281Q variant, our patients showed an atypical course of disease with alopecia totalis in the child and a complete lack of lung involvement in the mother. Conclusions Our findings demonstrate the phenotypic breadth of clinical SAVI manifestations. Given the therapeutic benefit of treatment with JAK inhibitors, early genetic testing for SAVI should be considered in patients with unclear systemic inflammation involving cutaneous, pulmonary, or musculoskeletal symptoms, and signs of immunodeficiency and autoimmunity.